Studi Kritis atas Qur’an: A Reformist Translation - Lukman, Fadhli (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
change-newline"> One of some translation works on the Qur’an appears to be eccentric concidering that it reveals some important revisions to traditional translation. This translation is written by Edip Yuksel, Layth Saleh al-Shaiban, dan Martha Schulte-Nafeh entittled Qur’an: A Reformist Translation. This article attempts to question the view of the writers of Qur’an: A Reformist Translation on historicity related to the Qur’an, framed with hermeneutical theory of Gadamer. The article ends to some conclussions that on their view, the Qur’an is a self-suffiient scripture, and therefore one has no need to seek the extra-Qur’anic aspect. Eventhough the writers deny the importance of historicity of the Qur’an, they indeed depend on the contemporary history which triggers their will to translate the Qur’an. As they deny the horizons of the text and rely on their own contemporary horizons, their approach then belongs to subjectivist hermeneutics.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />